(untitled) (Training and Practice : Journal of Educational Sciences, 2015)
The current scientific literature of both domestic and foreign sources indicates a large number of findings that examine many aspects of kindergarten children concerning their psychological and pedagogical features. Our work at hand aims at assessing the level of subcapabilities. Our other goal with this study is a strife for the methodological renewal of the kindergarten teacher education concerning its pedagogical and psychological aspects by offering good practices. Two-sided serial movement pattern, spatial orientation related to the child’s body perception, visual discrimination, visual memory, reproductive capability as well as spatial and sequential orientation are examined. Span and intensity of attention, verbal memory and memorisation, and the capability of ordering and composing are also in focus. Processing the data was done by the SPSS programme, with which we were examining averages, deviations, and significance. 65 kindergarten children were tested.